Attitude of Elementary School Students towards Mathematics Learning in Arunachal Pradesh - Singh, Vivek; Maga, Jumni (SCHOOL SCIENCE, 2020)
Mathematics is the science that draws the necessary conclusions, which is very important for our daily life activities. The present research aimed to study Class VIII students' attitudes towards mathematics in private and government schools in the Kamle District of Arunachal Pradesh. Descriptive-cum survey method has been used by applying simple random sampling. Sampling was done at two stages; firstly, six elementary schools were selected out of fifty, and at the second stage, twenty students were selected from each school. In this way, a total of 120 students were selected as respondents for the study. The attitude scale developed by Martha Tapia has been used for the survey. The study's finding reveals that Class VIII students show average attitudes towards mathematics. The attitude of boys was higher than girl students, on the other hand, no difference was found based on types of school (government and private school students).